2011
DOI: 10.1142/s0219635211002695
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Wi-Fi Signals on the P300 Component of Event-Related Potentials During an Auditory Hayling Task

Abstract: The P300 component of event-related potentials (ERPs) is believed to index attention and working memory (WM) operation of the brain. The present study focused on the possible gender-related effects of Wi-Fi (Wireless Fidelity) electromagnetic fields (EMF) on these processes. Fifteen male and fifteen female subjects, matched for age and education level, were investigated while performing a modified version of the Hayling Sentence Completion test adjusted to induce WM. ERPs were recorded at 30 scalp electrodes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 57 publications
0
11
0
3
Order By: Relevance
“…Three recent studies (Lustenberger et al, 2013;Schmid et al, 2012a,b) and several earlier studies cited in Wagner et al (1998) have each shown EEG changes in sleeping humans exposed to non-thermal pulsed microwave fields. Two recent studies showed EEG changes in persons exposed to Wi-Fi fields (Maganioti, 2010;Papageorgiou, 2011). Lai, 1997 described 8 animal studies showing changes in EEG patterns in animals exposed to non-thermal EMFs and three additional animal studies were described in Tolgskaya and Gordon, 1973.…”
Section: Discussionmentioning
confidence: 99%
“…Three recent studies (Lustenberger et al, 2013;Schmid et al, 2012a,b) and several earlier studies cited in Wagner et al (1998) have each shown EEG changes in sleeping humans exposed to non-thermal pulsed microwave fields. Two recent studies showed EEG changes in persons exposed to Wi-Fi fields (Maganioti, 2010;Papageorgiou, 2011). Lai, 1997 described 8 animal studies showing changes in EEG patterns in animals exposed to non-thermal EMFs and three additional animal studies were described in Tolgskaya and Gordon, 1973.…”
Section: Discussionmentioning
confidence: 99%
“…But acute detrimental effects on cognition were omitted from the report (22)(23)(24)(25) or mentioned in different sections (26)(27)(28)(29). Increased errors during a memory task (26), slowed performance (27) or decreased accuracy in a cognitive test (28) were reported in the electroencephalogram (EEG) section [pages 209-213 (2)]; slowed performance in cognitive tests (29) were reported under sleep [page 215 (2)].…”
Section: Scientific Accuracymentioning
confidence: 99%
“…Badanie to jest interesujące, ponieważ wskazuje na możliwość występowania efektów oddziaływania PEM, które zachodzą tylko podczas ekspozycji i są niewykrywalne po jej zakończeniu, podczas gdy w wielu badaniach realizowanych na świe-cie [41,42,51] analizowano potencjalny wpływ PEM, ale już po zakończeniu ekspozycji. Jedyne dotychczas badanie, w którym analizowano wpływ PEM emitowanego z routerów Wi-Fi na falę P300 [52], potwierdza w pełni wyniki opublikowane przez Bąka. Wykazano w nim, że w obecności PEM następowało zmniejszenie amplitudy fali P300 u mężczyzn, natomiast takiego efektu nie obserwowano u kobiet.…”
Section: Wpływ Pem Na Potencjały Wywołaneunclassified
“…Tylko pojedyncze publikacje, spośród wszystkich przeanalizowanych w niniejszym przeglądzie, dotyczyły rodzajów PEM innych niż telefonia komórko-wa. Były to prace, w których analizowano oddziały-wanie PEM emitowanego przez router Wi-Fi na układ nerwowy [52], wpływ PEM z radiowych i telewizyjnych stacji nadawczych na ryzyko zaburzeń funkcjonowania układu krążenia i autonomicznego układu nerwowego [56] oraz ekspozycję na sygnał radia TETRA i zwią-zane z nią subiektywne symptomy [64]. Wydaje się, że tak znaczne zmarginalizowanie w badaniach naukowych innych źródeł, mimo powszechnej i dominującej obecności telefonów komórkowych, jest znacznym zaniedbaniem.…”
Section: Wnioskiunclassified